Validity of Clinical Risk Index for Babies (CRIB) Score in Predicting the Neonatal Mortality - Abdul Rehman, Sana Jamil, Haseeb Arshad, Tayyaba Mushtaq, Amber Shabir, Asma Afzal, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the validity of Clinical Risk Index for Babies (CRIB) score in predicting the neonatal mortality in very preterm neonates. Methodology: The 145 patients enrolled in this study were registered from NICU of Children Hosp, Lahore, they were preterm neonates with gestational age of ≤ 32 weeks. We determined six parameters of CRIB score; gestational age, birth weight, any congenital malformation, minimum and maximum FiO2 requirementduring 1st 12 hours of life and maximum base excess during 1st 12 hours of life. All parameters were recorded and assigned an individual score base upon CRIB scoring chart. Total CRIB score was determined by adding individual score of each parameter. We reviewed thebabiesdaily in NICU till discharge or death. Results: Out of 145 patients, 52.4%(n=76)male and female were 47.59%(n=69). Congenital malformations were present in 6.21% (n=9), mortality in 36.55%(n=53). Mean gestational age was 29.90±1.70weeks, mean birth weight1147.52±190.21grams, mean maximum base excess during first 12h of life-8.04±3.92mmol/L, mean minimum appropriate FiO2 in first 12h34.3813.02 %, mean maximum appropriate FiO2 in first 12h69.17±21.11 % and mean CRIB Score was 4.63±3.67. AUR curve was 0.816 and std. error was recorded as =0.039;p=0.000. Conclusion: Mortality in very preterm neonates can be accurately predicted by using CRIB score.